2022
DOI: 10.1371/journal.pone.0278392
|View full text |Cite
|
Sign up to set email alerts
|

A genetic correlation and bivariate genome-wide association study of grip strength and depression

Abstract: Grip strength is an important biomarker reflecting muscle strength, and depression is a psychiatric disorder all over the world. Several studies found a significant inverse association between grip strength and depression, and there is also evidence for common physiological mechanisms between them. We used twin data from Qingdao, China to calculate genetic correlations, and we performed a bivariate GWAS to explore potential SNPs, genes, and pathways in common between grip strength and depression. 139 pairs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…In a groundbreaking study, Zhang et al [ 22 ] explored the shared genetic variation between depression and grip strength using twin data from Qingdao, China. They discovered potential genetic correlations, Single Nucleotide Polymorphisms (SNPs), genes, and pathways common to both conditions [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…In a groundbreaking study, Zhang et al [ 22 ] explored the shared genetic variation between depression and grip strength using twin data from Qingdao, China. They discovered potential genetic correlations, Single Nucleotide Polymorphisms (SNPs), genes, and pathways common to both conditions [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
“…In a groundbreaking study, Zhang et al [ 22 ] explored the shared genetic variation between depression and grip strength using twin data from Qingdao, China. They discovered potential genetic correlations, Single Nucleotide Polymorphisms (SNPs), genes, and pathways common to both conditions [ 22 ]. The study revealed a moderate genetic correlation between grip strength and depression, with a genetic correlation coefficient of -0.41 (-0.96, -0.15), indicating a shared genetic basis [ 22 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations